Distillation of Bioethanol from Nypa Using Flat Plate Solar Collector - Gerard Antonini Duma; Doddy Suanggana (Jurnal Teknik Mesin, 2018)
The study aims to investigate the production of bio-ethanol derived from sugar palm using flat plate solar collector, the bio-ethanol level based on different sugar palm liquid treatments, heat transfer in the collector, and compare the results of the two procedures of testing. The study method used is experiment by testing the bio-ethanol produced with two different testing methods. The experiment indicates that the first procedure yields 68 cc and the average production is 17 cc, with an ethanol concentration of 62,9%. The second procedure generate 49 cc and the average production is 16,3 cc with ethanol concentartion of 60,9%.